Preferences of Student Officers in Choosing a Seafaring Education and Training Institution - Bashori , Achmad; Suhartini, Suhartini; Inayaturrobbany; Ala, Asman (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
Knowledge of the preferences of student officers in choosing a shipping education and training institution is very important because it is closely related to the income of a shipping education and training institution. The more student officers (pasis) who register automatically increase their income as well. Some combined attributes of product variables and service variables that are the preferences of pasis in choosing a shipping education and training institution are in order (1) Teaching Staff, (2) Campus Location, (3) Education Costs, (4) Duration of Certificate Issuance, (5) Learning Methods, (6) Campus Physical Conditions, (7) Campus Accreditation, (8) Friendliness of Officers, (9) Ease of Website Access, (10) Response to Customer Complaints, (11) Campus Reputation, (12) Laboratory Facilities, (13) Alumni. Based on the utility value, all attributes of the product variable (Teaching Staff, Campus Location, Tuition Fees, Learning Methods, Physical Campus, Campus Accreditation, Campus Reputation, Laboratory Facilities, Alumni) affect the students' preferences in choosing a college / shipping education and training institution, while the service variable is only the duration of certificate issuance which affects the students' preferences in choosing a college / shipping education and training institution while officer friendliness, speed of handling customer complaints and speed of website access do not affect it.